Simulação de uma coluna de destilação para produção de etanol hidratado e análise de perdas na vinhaça e pureza do etanol produzido - Generoso, Bárbara Raissa (Universidade Federal de São Carlos, 2021)
The industrial distillation process is complex and since the adoption of ethanol as a fuel, replacing gasoline, it has become a strategic process for the country. Wines produced from fermentation have a concentration of 6.4 to 9.7% w/w of ethanol and commercial hydrous bioethanol must have a concentration of 92.6 to 93.8% w/w. Ethanol losses in vinasse and phlegmasse are important parameters during the operation of a distillery, as they determine the efficiency of the distillation process. Chemical process simulation software’s play an important role in the development of new processes and in the analysis of already consolidated processes, enabling testing hypotheses and comparisons with the reality of a plant in a practical, economically viable and assertive way. In the present work, the simulation software Aspen Plus® (Advanced System for Process Engineering), commercialized by Aspen Tech, was used. The work was intended to simulate a real distillation column to obtain hydrous bioethanol, considering a constant Murphree stage efficiency scenario associated with a 0.027% ethanol loss in the vinasse stream and a produced hydrous bioethanol content of 92.7% w/w. The consumption of steam obtained was 2.88 kg/L ethanol, it was observed that drops in steam pressure result in loss in vinasse and impact the purity of the ethanol obtained. The column reflux ratio determines the purity of the ethanol obtained and the optimal ratio is between 2.7 and 4.2. The simulated temperatures satisfactorily approached the operating temperatures, demonstrating that the simulation represents the real process.
Simulation of a distillation column for the production of hydrated ethanol and analysis of vinasse losses and ethanol purity
Simulación de una columna de destilación para la producción de etanol hidratado y análisis de pérdidas en la vinaza y pureza del etanol producido
Keywords: Destilação; Etanol; Simulação; Distillation; Ethanol; Simulation; ENGENHARIAS::ENGENHARIA QUIMICA::OPERACOES INDUSTRIAIS E EQUIPAMENTOS PARA ENGENHARIA QUIMICA